1999
DOI: 10.1002/(sici)1096-9861(19990428)407:1<77::aid-cne6>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

p75NTR immunoreactivity in the rat dentate gyrus is mostly within presynaptic profiles but is also found in some astrocytic and postsynaptic profiles

Abstract: To localize neurotrophin binding sites within the rat dentate gyrus, the distribution of low‐affinity p75 neurotrophin receptor (p75NTR) immunoreactivity (IR) was examined by using antiserum raised against the cytoplasmic domain of the receptor. Semiquantitative electron microscopic examination of p75NTR‐labeled sections showed that most p75NTR‐labeled profiles were axons and axon terminals (72% from a total of 3,975); p75NTR‐IR was observed throughout the extent of these structures and was not limited to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
46
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 89 publications
12
46
1
Order By: Relevance
“…However, recent evidence in vivo and in vitro also demonstrates dendritic spine localization of p75 NTR in CA1 and dentate gyrus of hippocampal neurons (19,23,85,86). In accordance with these studies, we found colocalization of p75 NTR with MAP2 and PSD95 in hippocampal pyramidal neurons of CA1, revealing a postsynaptic localization of p75 NTR .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, recent evidence in vivo and in vitro also demonstrates dendritic spine localization of p75 NTR in CA1 and dentate gyrus of hippocampal neurons (19,23,85,86). In accordance with these studies, we found colocalization of p75 NTR with MAP2 and PSD95 in hippocampal pyramidal neurons of CA1, revealing a postsynaptic localization of p75 NTR .…”
Section: Discussionsupporting
confidence: 91%
“…Besides p75 NTR expression in neurons, it has been reported that astrocytes induce p75 NTR expression after different types of injury (36,86,87). Increased levels of p75 NTR have been detected in both neurons and astrocytes in the hippocampal CA3 region after seizures (37).…”
Section: Discussionmentioning
confidence: 99%
“…The p75 receptor is distributed throughout the dentate in a pattern resembling the AChE-containing septodentate input (Peterson et al, 1994). In addition, the p75 and the TrkA receptors are distributed in the dentate similarly to the septal input (Sobreviela et al, 1994;Dougherty and Milner, 1999;Barker-Gibb et al, 2001). The colocalization of p75 and TrkA in the septal fibers may be an important property dictating the probability of high-affinity binding (Hempstead et al, 1991;Esposito et al, 2001) and the consequent proliferation of cholinergic synapses.…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, this precursor of BDNF had been considered to be inactive; however, new evidence has suggested that pro-BDNF interacts with its own distinct receptor, the p75 neurotrophin receptor (p75 NTR ) (Lee et al 2001). p75 NTR is primarily localized on axons and axon terminals (Dougherty and Milner 1999), as well as dendritic spines in the CA1 region (Woo et al 2005) and has been implicated with numerous roles in the CNS, including apoptosis, axon elongation, and synaptic transmission (Dechant and Barde 2002). Recent evidence has proposed that p75 NTR , via pro-BDNF, may also affect synaptic plasticity.…”
Section: Exercise Neurotrophins and Synaptic Plasticitymentioning
confidence: 99%